Χρήση ανθεκτικών ποικιλιών για την αντιμετώπιση του κυστονηματώδη της πατάτας Globodera rostochiensis - Παπαμιχαήλ, Σωτηρούλλα (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων , Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2012)
Potato cyst nematodes (PCN), Globodera pallida (Stone) Behrens and G. rostochiensis (Wollenweber) Behrens are considered to be responsible for major losses in several potato growing areas of the eastern part of Cyprus. To alleviate losses, growers make excessive use of nematicides having a negative impact on both the environment and human health. Furthermore, growers attempt to use resistant varieties without knowing the level of resistance or the target species or pathotypes. The present study aims towards the integrated management of PCN through the utilisation of potato varieties (Annabell, Arinda and Allians) resistant to G. rostochiensis pathootype Ro1 and the combined use of two nematicides, fosthiazate and oxamyl. Variety Spunta was used as a control. Resistant varieties showed a decrease in the population density of PCN in the soil whereas the susceptible variety Spunta showed ten times increase on the population density. In all treatments, nematicides showed a decrease in the population density in the soil. Resistant varieties yielded well with the variety Arinda showing the highest yield among the three resistant varieties. Similar resuslt were found with regard to tuber size. Variety Spunta showed a significant reduction of yield and tuber size. Nematicides gave similar results in all treatments and in all four varieties tested wheareas nematode population densities decreased and yield remained at acceptable levels.
Keywords: Disease; Potatoes; Ασθένειες; Πατάτες